Стимулирование воспроизводительной способности молодых самок соболей фермерских популяций - Сергеев, Е.Г.; Сафронова, Л.Д. (Фактори експериментальної еволюції організмів, 2013)
The purpose of research is to study how to promote young female reproductive function sables. The method of regular spiking in the spring of mature males to one-and two-year females with subsequent analysis of the behavior of couples. The results showed that the two-year females to be more active compared to the same age, as evidenced by the frequency and nature of contacts with males. Conclusions. Spring contacts of adult males with young females do not lead to increased sexual function sobolyushek and do not affect the course of the summer breeding season, cases fit males during the experiment are elements of the game, not sexual behavior, the greatest effect on the reproductive function of young females had their prolonged detention (December to August) next to sexually mature males.

Key words: females sable, reproductive ability, farming populations.